Community Empowerment Assistance Based on Tourism Potential in Cibiru Tourism Village - Rachmat Astiana; Titing Kartika; Muhammad Iqbal Tawakal (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2022)
Cibiru is one of the sub-districts in the east of the city of Bandung and located at the foot of Mount Manglayang, has been blessed with various kinds of extraordinary natural, cultural and craft resources. Natural wealth in the form of hilly areas, agricultural plantations and abundant water resources. Some areas have also been arranged in such a way by the relevant parties from what were originally in the form of shrubs to green open spaces and beautiful gardens which can also be used for tourism activities. In addition, this sub-district also has the largest arts and culture group in the city of Bandung, which maintains many traditions and cultures that have been passed down from generation to generation and maintains the typical arts of West Java such as Silat, Benjang, Reak and so on. Tourism activities in Cibiru have not been managed properly because there is no legal management to carry out tourism activities. In addition to the absence of mapping and packaging of tourism potential that is owned so that it does not yet have a selling value that can provide economic benefits for the surrounding community. This service activity is carried out as part of an effort to help empower the community so that all tourism potential that is owned can provide great value for the community. The activities carried out are in the form of tourism management training and workshop activities to identify superior tourism potential so that a mapping of tourism potential is obtained as outlined in a tourist map as well as making simple tour packages that can be used as basic capital in marketing tourism potential